Exploring Attitudes Toward Egg Consumption During Pregnancy in Kenya (P10-054-19). (13th June 2019) - Schnefke, Courtney; Lutter, Chessa; Thuita, Faith; Webale, Albert; Flax, Valerie; Bentley, Margaret
Abstract: Objectives: Eggs are nutrient-rich and have the potential to improve maternal nutrition during pregnancy and birth outcomes, but cultural beliefs may inhibit consumption during pregnancy. This study sought to understand pregnant women's and key influencers' knowledge, attitudes, beliefs, and practices as well as facilitators and barriers related to consuming eggs during pregnancy in Kenya. Methods: The study was conducted in an urban (Nairobi) and rural (Kiambu) area, had 3 phases and primarily used mixed qualitative methods to triangulate data. Phase I included in-depth interviews, 24-hour dietary recall, and free-listing and pile-sorting exercises with pregnant women ( n = 36), husbands ( n = 12) and mothers-in-law ( n = 12) of pregnant women, and health workers ( n = 24). Phase II involved egg preparation exercises with pregnant women ( n = 39). Phase III involved a week-long trial of egg consumption with pregnant women ( n = 24). We used thematic content analysis methods to analyze qualitative data and tabulated quantitative data. Results: All participants recognized eggs as nutritious for pregnant women and their unborn children, though only 25% of pregnant women consumed eggs the previous day. Participants believed eating too many eggs during pregnancy (1 or more eggs daily) leads to a large baby and complications during delivery. Unaffordability and unavailability of eggs also inhibit consumption. Health workers are the most trusted source of information on maternal nutrition, while other pregnant and nonpregnant women in the community were cited as those who most often discourage egg consumption. Fried and boiled eggs are the most common and preferred preparation methods due to ease and limited number of ingredients. Almost all women complied with the household trial, said they would continue eating eggs during pregnancy, and would recommend consuming eggs in moderation to other pregnant women. Conclusions: Although participants believed consuming eggs during pregnancy is beneficial, cultural norms, practices, and beliefs may prevent pregnant women from eating them daily. Interpersonal communication from health workers and agricultural policies to promote affordability could lead to increased consumption, which in turn could have potential positive impacts on maternal nutrition and birth outcomes. Funding Sources: RTI International.